Optimizing the enzymatic release of MMAE from isoDGR-based small molecule drug conjugate by incorporation of a GPLG-PABC enzymatically cleavable linker - Zambra, Marco; Ranđelović, Ivan; Talarico, Francesco; Borbély, Adina; Svajda, Laura; Tóvári, József; Mező, Gábor; Bodero, Lizeth; Colombo, Sveva; Arrigoni, Federico; Fasola, Elettra; Gazzola, Silvia; et al. (Frontiers in Pharmacology, 2023)
Antibody-Drug Conjugates (ADCs) and Small Molecule-Drug Conjugates (SMDCs) represent successful examples of targeted drug-delivery technologies for overcoming unwanted side effects of conventional chemotherapy in cancer treatment. In both strategies, a cytotoxic payload is connected to the tumor homing moiety through a linker that releases the drug inside or in proximity of the tumor cell, and that represents a key component for the final therapeutic effect of the conjugate. Here, we This is a provisional file, not the final typeset article show that the replacement of the Val-Ala-p-aminobenzyloxycarbamate linker with the Gly-Pro-Leu-Gly-p-aminobenzyloxycarbamate (GPLG-PABC) sequence as enzymatically cleavable linker in the SMDC bearing the cyclo[DKP-isoDGR] αVβ3 integrin ligand as tumor homing moiety and the monomethyl auristatin E (MMAE) as cytotoxic payload led to a 4-fold more potent anti-tumoral effect of the final conjugate on different cancer cell lines. In addition, the synthesized conjugate resulted to be significantly more potent than the free MMAE when tested following the "kiss-and-run" protocol, and the relative potency were clearly consistent with the expression of the αVβ3 integrin receptor in the considered cancer cell lines. In vitro enzymatic cleavage tests showed that the GPLG-PABC linker is cleaved by lysosomal enzymes, and that the released drug is observable already after 15 minutes of incubation. Although additional data are needed to fully characterize the releasing capacity of GPLG-PABC linker, our findings are of therapeutic significance since we are introducing an alternative to other well-established enzymatically sensitive peptide sequences that might be used in the future for generating more efficient and less toxic drug delivery systems.